2008
DOI: 10.1038/sj.bjp.0707630
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms underlie the analgesic actions of paracetamol and dipyrone in a rat model of inflammatory pain

Abstract: Background and purpose: The analgesics, paracetamol and dipyrone are weak inhibitors of the cyclooxygenase isoforms 1 or 2 (COX-1, COX-2) but more potent on COX-3. Both are also weak anti-inflammatory agents, relative to their analgesic and antipyretic activities. In a model of inflammatory pain mediated by prostaglandins, both compounds were analgesic. We have analysed this shared effect further in order to elucidate the underlying mechanisms. Experimental approach: Inflammation was induced in one hind paw of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
4
40
0
7
Order By: Relevance
“…It has been suggested that prostaglandins may play a role in these conditions, particularly in the vasodilatation, resulting in flushing (20). The antifebrile agent we used was acetaminophen, which has inhibitory activity to prostaglandins and cyclooxygenase isoform 3 (21,22). The dose of cetirizine, a second-generation H 1 antihistamine, in this study was high (10 mg) when compared with the recommended dosage of 5 mg/day for allergic symptoms (23).…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that prostaglandins may play a role in these conditions, particularly in the vasodilatation, resulting in flushing (20). The antifebrile agent we used was acetaminophen, which has inhibitory activity to prostaglandins and cyclooxygenase isoform 3 (21,22). The dose of cetirizine, a second-generation H 1 antihistamine, in this study was high (10 mg) when compared with the recommended dosage of 5 mg/day for allergic symptoms (23).…”
Section: Discussionmentioning
confidence: 94%
“…Atualmente, a dipirona e o paracetamol são os analgésicos mais prescritos no Brasil 11,12 ; no entanto, a dipirona tem seu uso restrito nos EUA e em vários países da Europa, em razão da possibilidade de causar agranulocitose, complicações gastrointestinais, anemia aplástica e anafilaxia 13,14 .…”
Section: Introductionunclassified
“…Acute administration of paracetamol has been shown to cause antidepressant-like effects and display synergistic effect with fluoxetine in FST and tail suspension tests without affect locomotor activity [27]. Dipyron and paracetamol have been proposed to reveal similar analgesic mechanism such as inhibition of COX enzymes in the brain, interaction with endogenous opioid and cannabinoid systems, arginine-nitric oxide-cGMP pathway, 5-HT activation [6]. Impairments in these endogenous systems also produce depressive states as indicated in clinically and experimentally studies [28].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonergic-noradrenergic system, arginine-NO-cGMP pathway, neuronal potassium channels and inflammatory cytokine levels have been suggested as possible mechanisms for the analgesic action of dipyrone [4][5][6]. Other central effects, distinct from this analgesic effect, have been evaluated.…”
mentioning
confidence: 99%